Clinical practice of a novel molecular diagnostic method for detecting Helicobacter pylori and clarithromycin resistance - Kameoka, Eisuke; Hikichi, Takuto; Kanno, Yukiko; Konno, Naoki; Kato, Tsunetaka; Yanagita, Takumi; Kodama, Kenta; Irie, Hiroki; Ohira, Hiromasa; Goto, Sayuri; Otsuka, Mitsuru; Kuroda, Masahito; et al. (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2025)
AbstractObjective: The Smart GeneTM system enables the rapid polymerase chain reaction-based detection of Helicobacter pylori (H. pylori) in gastric juice and determines clarithromycin (CAM) resistance. This study evaluated the clinical utility of the Smart GeneTM system for diagnosing and managing H. pylori infection.Methods:H. pylori diagnosis was obtained using the Smart GeneTM system and the effectiveness of individualized eradication therapy was evaluated. Treatment regimens were chosen based on CAM sensitivity in the Smart GeneTM test.Results: A total of forty-nine patients were assessed. Among them, 28 had H. pylori infection, while 3 had CAM resistance. Seventeen patients underwent H. pylori eradication therapy. Fourteen patients with CAM-sensitive strains underwent eradication therapy with vonoprazan (VPZ), amoxicillin (AMPC), and CAM. Two patients with CAM-resistant strains were treated with VPZ and AMPC, while one received VPZ, AMPC, and metronidazole. The eradication achievement rate was 100%. Of 31 outpatients, 61.5% began H. pylori eradication therapy on the same day as the Smart GeneTM test.Conclusion: Smart GeneTM enables rapid diagnosis of H. pylori infection and the detection of CAM resistance, allowing for personalized eradication regimens.